STUDENT ACHIEVEMENT IN FINAL ASSESSMENT THROUGH THE IMPLEMENTATION OF BLENDED LEARNING IN CLOUD-BASED LEARNING ENVIRONMENT - Mohd Norafizal Abd Aziz; Juhaida Ismail; Rozeleenda Abdul Rahman; Razulaimi Razali (Journal of Islamic, Social, Economics and Development, 2023)
Online learning implementation has emerged as the best alternative to traditional teaching during the pandemic era. This is supported by the blended learning mechanism, which effectively facilitates online learning. Furthermore, cloud-based learning environments provide diverse, borderless learning platforms capable of supporting online learning. However, this approach is less favoured due to user perceptions that prioritize systematic face-to-face learning. Therefore, this study aims to examine the effectiveness of online learning using the blended learning mechanism in a cloud-based learning environment, with a focus on students' final assessment achievements. Data collection was carried out through a case study at UiTM Branch Pahang, Raub Campus, involving second-semester students in the Computer Science Diploma program. The findings reveal significantly positive performance implications, with an average student achievement comparison between two groups ranging from 0.51 to -5.07 compared to the overall average of 20.6. The comparison of overall achievement between these student groups and another group will be discussed in this study. Therefore, this alternative approach has the potential to provide positive implications for online learning and change the negative perception towards online learning implementation. It also offers insight into continuous improvements that educational institutions can make to enhance the quality of education, particularly in flexible higher education settings.